(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Nanocrystalline NiCexFe2-xO4 (x = 0, 0.2, 0.4 and 0.6) magnetic spinel materials were synthesized by a simple microwave combustion technique (MCT) by utilizing the fuel of Pedalium murex plant extract. The establishment of a cubic spinel structure was ensured by powder X-ray diffraction (PXRD) technique and the crystallites size was found to be in the range of 27.5 to 13.1 nm for NiFe2O4 and Ce:NiFe2O4 nanoparticles (NPs). The morphology of the NiFe2O4 NPs was observed by high resolution scanning electron microscope (HR-SEM). Energy dispersive X-ray (EDX) studies confirmed the formation of pure spinel ferrite structure as they ensured the presence of all the elements and the formation of the desired compositions. Furthermore, the bandgap value was estimated to be within 3.26 and 3.39 eV. The appearance of Fourier transform infrared (FT-IR) bonds at 437 and 456 cm-1 is linked to the octahedral (B) metal stretching (Ni-O) and the band at 582 cm-1 is linked to the tetrahedral (A) metal stretching (Fe-O), which ensure the formation of cerium substituted NiFe2O4 NPs. Magnetic parameters such as remanent magnetization (Mr), coercivity (Hc) and saturation magnetization (Ms) were calculated from M-H loops, which exhibited ferromagnetic behaviour. The photocatalytic (PC) behavior of NiFe2O4, NiCe0.2Fe1.8O4, NiCe0.4Fe1.6O4 and NiCe0.6Fe1.4O4 were analyzed under visible light irradiation by the degradation (PCD) of an aqueous solution of Rhodamine B (RhB) dye. Among the various prepared compositions, NiCe0.4Fe1.6O4 exhibits higher PCD efficiency as 93.88 % at 120 min with enhanced visible light absorption range. The antibacterial activities of gram-positive Staphylococcus aureus, Bacillus subtilis and gram-negative Escherichia coli and Klebsiella pneumonia have been investigated using pure and Ce3+ substituted NiFe2O4 NPs. It was found that the improved activity is intensified with smooth Ce3+ doping as it cause a decrease in the grain size.